2019
DOI: 10.1109/lra.2019.2894380
|View full text |Cite
|
Sign up to set email alerts
|

Relaying the High-Frequency Contents of Tactile Feedback to Robotic Prosthesis Users: Design, Filtering, Implementation, and Validation

Abstract: It is known that high frequency tactile information conveys useful cues to discriminate important contact properties for manipulation, such as first-contact and roughness. Despite this, no practical system, implementing a Modality Matching paradigm, has been developed so far to convey this information to users of upper-limb prostheses. The main obstacle to this implementation is the presence of unwanted vibrations generated by the artificial limb mechanics, which are not related to any haptic exploration task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…For prostheses, it has been proposed to transmit grasp force by a proportional pressure applied by tactors on the residual arm [14], [15], thereby making the feedback more intuitive [16], [17]. Such modality matching, however, is not possible for all human-machine interfaces (e.g., replacing visual feedback).…”
Section: Introductionmentioning
confidence: 99%
“…For prostheses, it has been proposed to transmit grasp force by a proportional pressure applied by tactors on the residual arm [14], [15], thereby making the feedback more intuitive [16], [17]. Such modality matching, however, is not possible for all human-machine interfaces (e.g., replacing visual feedback).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that when the feedback signal is not congruent or is in conflict with vision, it is not integrated in the motor control strategy [ 27 , 57 ]. Here, although our feedback was not modality-matched in the sense of a stimulus that would be felt in the same modality as the initial sensory information [ 25 , 58 ], it was designed to be as intuitive as possible, with elbow rotation directly translated into a rotation of the vibration around the arm. In Guemann et al [ 31 ], we showed that tactile perception was better with this circular arrangement of vibrors on the arm than with a longitudinal one, probably due to the increased likelihood of stimulating different dermatomes and mechanoreceptive units whose oval-shaped receptive fields are oriented in the longitudinal axis [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Closing the loop between action and perception involves three key aspects, according to Antfolk et al [3]: (i) accurate sensors, (ii) reliable actuators and (iii) a tactile elicitation that allows an intuitive re-learning and adaptation of the Central Nervous System to the delivered inputs. Recent advances address point (ii) through the development of novel actuation methods [12], [13] and (iii) through non-invasive [14], [15] and invasive haptic feedback paradigms [16]. Here, we focus on point (i), the development of tactile sensors and their integration with robotic hands.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Soft actuation introduces challenges when it comes to sensitizing the hand with tactile or proprioceptive capabilities, with classical solutions not being applicable due to the absence of rigid links. Proposed solutions have included the use of flexible strain sensors [19] in continuum soft robot hands and IMUs [15], [20] or motor encoder values [21] in soft articulated hands. Here our aim is to develop technologies and methods around neuromorphic sensing that could integrate with a soft articulated hand and lead to the sensitization of upper-limb prosthesis and telerobotics.…”
Section: Background and Related Workmentioning
confidence: 99%